Smart Trash Untuk Membantu Petugas Kebersihan Menggunakan Arduino - Riesky Akbar; Djoni Haryadi Setiabudi; Handry Khoswanto (Jurnal Infra, 2020)
Many times, the garbage bins at public places are overloaded even exceeding capacity or overflow which creates unhygienic conditions for people as well as ugliness to that place and leaving bad smell. The full garbage bins are left to pile up and wait until they are taken back by the janitor. To avoid that kind of situation, a smart trash is made for assisting the janitor to monitoring the level content of the garbage bins. Navghane [5] has created a smart trash that can monitoring level of garbage by the web browser. This thesis will create a smart trash system with push notification by a smartphone application that will be easier for janitors pick up the garbage bin just in time.The garbage bin is installed with Arduino WeMos D1 R1 system and proximity sensor E18-D80NK which will show the status of the garbage at the current level. Data obtained from the sensor will be sent with a microcontroller that connected with Wi-Fi to the database. That will be data exchange in real-time between an application on the user’s smartphone with the smart trash device.The result of this thesis is the device can detect and show the garbage level in real-time with percentage and 2D images on the smartphone application, and provide a push notification that appears when the garbage level has full or reached the upper limit. Proximity sensor E18-D80NK is prone to detect dry trash, which is transparent and thin, but can detect dry trash which are solid and not transparent.